BEARING CAPACITY ASSESSMENT OF PILE FOUNDATION BETWEEN THE DYNAMIC FORMULA AND PDA TEST - Muhammad Toyeb; Zainuri (Racic : Rab Construction Research, 2025)
A pile foundation is essential in providing the bearing capacity and stability of the up-structure. This study uses three dynamic formulas such as Hilley, Janbu, and Engineering New Record. The aim of the study is to find an accurate formula for bearing capacity that close the PDA test. Analyses the bearing capacity to two pile numbers of 251 and 120. Subsequently, the result of the PDA test provides the pile's bearing capacity for 251 is 85.2 tons, and for 120, it is 72.0 tons. The assessment of piles showed that the Janbu formula was more accurate than Hilley and ENR because it was nearest to the PDA test result. Therefore, the Janbu formula can be used as an alternative method if the PDA test is unavailable. Meanwhile, with the Hilley formula, the bearing capacity is lower than the PDA test, and it needs to be corrected for the safety factors. Meanwhile, the ENR formula obtains the bearing capacity as higher of Janbu and Hilley.